Bahasa Inggris - Almubarok, Fahad Farhan; Muthasina, Faisal Yahya; Darwis, Muhammad; Purnama, Diki Gita (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
IOTA (Foster Parent Information Application) is a mobile system designed to facilitate communication between foster parents, foster children, and related institutions. Using the waterfall method, the application development includes implementation, testing, and maintenance phases. Requirements analysis determines key features such as daily activity recording, while an intuitive user interface design and efficient database architecture are implemented according to specifications. Comprehensive testing is conducted to ensure optimal performance. It is hoped that through this process, IOTA will enhance communication and care for foster children through a more effective platform. Keywords: Foster Parent Information Application (IOTA), Waterfall Method, Foster Parent Communication, Mobile Application Development, Coordination of Related Institutions